Race at predominantly white independent schools : the space between diversity and equity - French, Bonnie E. (Lexington Books, 2018)
In this book, French compares the "well-meaning" intensions of "diversity" in independent schools with the continued dominance of whiteness in these institutions. Using mixed methods and a Critical Race Theory frame, French argues that "diversity" serves only to strengthen the status quo of educational segregation between Black and White